Valuation of Provisioning Ecosystem Services Carat Cape Mangrove for Sungsang IV Village Community Banyuasin District - Ahmad Panandi; Andy Mulyana; Bernadette Robiani (Sriwijaya Journal of Environment, 2019)
Mangrove ecosystem valuation can be used as a reference for decision making for management and conservation of mangrove ecosystems in a sustainable manner. The range of activities and interests conducted in coastal areas is not expected to negatively impact the ecology, economic and social. Carat Cape mangrove areas provide enormous benefits to the surrounding community, especially Sungsang IV village. From the results of the study illustrate the provosioning ecosystem service utilized community Sungsang IV village consists of materials construction (timber and nypa leaves), a source of livelihood or subsistance (nypa fruit, fish, shrimp, crab, and scallops). The total value of provosioning ecosystem services mangrove Carat Cape utilized by the Sungsang IV village Rp. Rp. 1.715.590.000, - per year dominated by income generated by marine species of fish which is the main livelihood of the fishermen Sungsang IV village  reached Rp. 1.302.600.000,- per year.